Two-Scale Modelling of Reactive Powder Concrete. Part III: Experimental Tests and Validation - DENISIEWICZ, Arkadiusz; KUCZMA, Mieczysław Sylwester (Engineering Transactions, 2015)
This article is the third and final part of a series about two-scale modelling of reactive powder concrete in the linear range. In the first part [1] a method of modelling RPC microstructure was presented, the boundary value problem of mechanics for a representative cell at the micro scale was formulated and solved. In the second part [2] a method for determining material parameters at the macro level was shown, a technique for enforcing boundary conditions upon an RVE was described, and the results of numerical simulations were presented. In this part we will present the results of laboratory tests of full-size beams made from two RPC mixtures, the results of numerical simulations of these beams and the validation of the proposed numerical model.